Predicting ocular injury in the setting of pediatric orbital fractures - Welcher, Jennifer; Armstrong, Mikhayla L.; Serina, Anthony J.; Gaier, Eric; Neuman, Mark; Miller, Andrew; Shah, Ankoor S. (Digital Journal of Ophthalmology, 2024)
Introduction A recent study suggested a targeted approach to ophthalmic consultation in the setting of orbital fractures (OF) in the adult population.1 However, pediatric cases have not been studied, and thus the approach to ophthalmic consultation may be inconsistent. This study aims to identify factors that may suggest high risk of ocular and muscle injury in the setting of pediatric OFs. Methods This retrospective study queried Boston Children’s Hospital billing data to identify patients ≤18 years diagnosed with OF in the emergency department between 07-01-2011 – 06-30-2020. To be included, a comprehensive ophthalmology examination had to be performed within 24 hours of injury. Historical details and clinical examination findings were abstracted from the chart. Ocular injury was defined as any abnormal finding on the eye examination that would be associated with trauma. Results One-hundred-sixty-seven patients with 172 total OFs met inclusion. Seventy (41.9%) patients suffered right OFs, while 92 (55.1%) suffered left OFs. Five suffered bilateral fractures. The cohort’s average age at injury was 12.4 years and was primarily male (80.2%). Multivariable logistic regression identified blunt injury with a foreign object (P < 0.001), eye pain with movement (P = 0.014), supraduction motility restriction (P = 0.016), and abnormal pupillary light reflex (P = 0.104) as factors with increased likelihood of associated ocular injury. Applying the four variables clinically showed a sensitivity of 90.4%, specificity of 56.7%, PPV of 47.5%, and NPV of 93.2%. The area under the curve of the receiver operator characteristic curve (ROC) was 0.809. Conclusions Pediatric orbital fractures may be associated with significant ocular injury, and historical and examination findings may supplement the clinical acumen of emergency physicians on when to request urgent ophthalmology consultation. Future studies might test these four independent predictors of substantial ocular injury on a validation cohort. Additionally, a multi-center, prospective study might allow generalization of these findings.